2007
DOI: 10.1080/08860220701641199
|View full text |Cite
|
Sign up to set email alerts
|

Local Calcitriol Injections as a Suppressive Treatment of Secondary Hyperparathyroidism in Chronic Dialysis Patients

Abstract: Parathyroid adenoma injection is an alternative method of treatment for some patients resistant to treatment by means of vitamin D3 pulses or intravenous administration of calcitriol. The success of treatment is to a great extent determined by proper selection of patients and the taking of decisions when the period of secondary hyperparathyroidism is not very advanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Several case reports and case series have been published. Percutaneous injection of ethanol [21,22], acetic acid [23] and calcitriol [24] and thermal ablation, including radiofrequency (RF) [25,26], laser [27] and high-intensity focussed ultrasound (HIFU) [28,29], have been assessed in patients with hyperparathyroidism. A preliminary study by our group also confirmed that ultrasound-guided MWA was safe and effective in destroying parathyroid gland tissue in patients with SHPT [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports and case series have been published. Percutaneous injection of ethanol [21,22], acetic acid [23] and calcitriol [24] and thermal ablation, including radiofrequency (RF) [25,26], laser [27] and high-intensity focussed ultrasound (HIFU) [28,29], have been assessed in patients with hyperparathyroidism. A preliminary study by our group also confirmed that ultrasound-guided MWA was safe and effective in destroying parathyroid gland tissue in patients with SHPT [15,16].…”
Section: Discussionmentioning
confidence: 99%